Greenhouse evaluation of in vitro-characterized plant growth-promoting Pseudomonas strains on the growth of Sorghum bicolor seedlings - Teshome, Befekadu; Belay, Belay; Tsegaye, Zerihun (Food Agricultural Sciences and Technology, 2026)
Plant growth-promoting rhizobacteria play a vital role in sustainable agriculture by supporting plant development and stress resilience. This study investigated the effects of selected bacterial strains on the growth of Sorghum bicolor seedlings under controlled greenhouse conditions. Four elite in-vitro-characterized plant growth-promoting Pseudomonas strains were assessed for their potential to enhance biomass accumulation, root and shoot length, and leaf chlorophyll content of two local varieties (Zengada and Degalit) of Sorghum bicolor seedlings. The four-plant growth-promoting Pseudomonas strains included were P. extremorientalis, P. brenneri, P. simiae, and P. fluorescens. The greenhouse evaluation was conducted for 17 treatment groups, which were derived from the four Pseudomonas strains and one control. The bacterial treatments had significant effects on a greater number of parameters on Sorghum Zengada variety than the Sorghum Degalit variety. The treatments showed significant effects on the length of shoot and root, and leaf chlorophyll contents of both varieties. But they showed significant effects only on shoot dry weight and leaf width of Zengada variety (P < 0.05). Treatment BCD (A combination of P. extremorientalis, P. simiae, and P. fluorescens) showed a significant effect on Zengada sorghum’s shoot dry weight (3.83 ± 1.68 g) and leaf width (2.67 ± 0.49 cm) compared to the control with 1.12 ± 0.33 g and 1.27 ± 0.2 g, respectively. It also performed well in Degalit sorghum in terms of shoot length (86.3 ± 1.80 cm) compared to the control with 41.87 ± 5.51 cm, making it a strong candidate for bioinoculant development through field trials.